1991
DOI: 10.1007/bf03160996
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid metabolites and enzymes in rat brain due to ischemia and recirculation

Abstract: Thirty and 60-min ischemic insults resulted in an increase in free fatty acid and 1,2-diacylglycerol contents of rat forebrain. No significant changes were detected in phospholipids except phosphatidylinositol 4-monophosphate and phosphatidylinositol 4,5-bisphosphate during ischemic insult. Phosphatidylinositol 4-monohosphate and phosphatidylinositol 4,5-bisphosphate contents decreased during ischemia. Although the increase in free fatty acid contents continued, 1,2-diacylglycerol did not show further increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Some studies showed a significant decrease in the content of brain phospholipids [810, 37], whereas other studies found no change [11, 13], even after 60 min of ischemia [12]. These contradictory findings suggest that ischemia alone is not sufficient to cause significant phospholipid alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed a significant decrease in the content of brain phospholipids [810, 37], whereas other studies found no change [11, 13], even after 60 min of ischemia [12]. These contradictory findings suggest that ischemia alone is not sufficient to cause significant phospholipid alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal membrane breakdown and/or turnover has been implicated in several human brain disorders including Alzheimer's disease (2,3), cerebral ischemia (4,5), schizophrenia (6)(7)(8), and cerebellar ataxia (9,10). This has prompted some investigators to consider the use of inhibitors of membrane breakdown or stimulators of membrane synthesis as potential therapeutic agents in these diseases.…”
mentioning
confidence: 99%
“…As described, prominent changes in lipids are reportedly accompanied in the ischemic brain, where a rapid decrease in phosphatidylinositol-4,5-bisphosphate (PIP 2 ) levels together with a parallel accumulation of diacylglycerol (DG) is observed (Kunievsky et al 1992). In addition, levels of PIP, PIP 2 , and DG approach plateau values after 10 min of ischemia ), a 30 min recirculation period after 15 min of ischemia engenders increases in PIP and PIP 2 , whereas levels of DG decrease promptly toward control values (Moto et al 1991;Yoshida et al 1986). Detailed analysis of lipid changes in distinct subcellular compartments should help to determine how DGK cytoplasmic translocation is implicated in DG metabolism, although it might be diYcult because of the rapid changes.…”
Section: Discussionmentioning
confidence: 91%